Performance of integrated milk co-operatives - Rande, C.G...[et.al] (New Delhi, 1988)
This is a unique study on Amul, the Cooperative Milk Producer's Union in Kaira district, which is a model of integrated rural development. Beginning with the birth of the dairy industry in Kaira in 1946, the book traces the formative years of the district cooperative within the context of the general economic, social and political conditions in the district. It examines the inputs and investments in the growth of the Union, the relations between the Union, the Bombay Milk Scheme, the Government of India and international organisations, and its contribution to the upliftment of the entire district. The book has policy implications of a significant nature for all rural economic development plans in India and other developing countries.
Keywords: Cooperative marketing